Intake and digestion of urea-treated, urea-supplemented and untreated rice straw by goats - Tuen, A.A.; Dahan, M.M.; Young, B.A.; Vijchulata, P. (Elsevier, 1991)
The intake and digestion by goats of urea-treated rice straw and untreated straws given alone or supplemented with urea were measured in a Latin square design study. Intake was measured when the straws were offered ad libitum. Digestibility and nitrogen (N) balance of the diets were measured at 85% of the ad libitum intake. Organic matter intake (45.2 g kg-1 W0.75) and digestibility (578 g kg-1) of the total diet were higher for urea-treated straw than for supplemented straw (39.4; 534) or straw alone (41.1; 527). Urea supplementation of untreated straw had no significant effect on intake or digestibility. Rumen ammonia levels were similar in goats fed on urea-treated (42.7 mg l-1) and urea-supplemented (39.7 mg l-1) straw, and were much higher than those in goats fed on untreated straw (25.7 mg l-1). The positive response to urea-treated straw was thought to be due to its higher N content in the presence of higher digestible energy. The urea treatment apparently caused a change in the physical and chemical structure of the straw, resulting in increased digestible organic matter intake, whereas urea-added to the diet immediately before it was consumed did not affect intake or digestibility.